2009
DOI: 10.1016/j.cplett.2009.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Polarizabilities as a test of localized approximations to the self-interaction correction

Abstract: We present applications of the recently introduced "Generalized SIC-Slater" scheme which provides a simple Self-Interaction Correction approximation in the framework of the Optimized Effective Potential. We focus on the computation of static polarizabilities which are known to constitute stringent tests for Density Functional Theory. We apply the new method to model H chains, but also to more realistic systems such as C 4 (organic) chains, and less symmetrical systems such as a Na 5 (metallic) cluster. Compari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…Early calculations using SIC applied to the local (spin) density approximation (LSDA) found that polarizabilities for closed-shell atoms are reduced by removing self-interaction. [3,4] Other SIC studies focused on the polarizability of long chain-like molecules [5][6][7] where again it was found that eliminating SIE reduces DFA polarizabilities and brings them into better agreement with reference values. More recently, SIC polarizabilities were computed to investigate the nature of the bonding in Na(H 2 O) n complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Early calculations using SIC applied to the local (spin) density approximation (LSDA) found that polarizabilities for closed-shell atoms are reduced by removing self-interaction. [3,4] Other SIC studies focused on the polarizability of long chain-like molecules [5][6][7] where again it was found that eliminating SIE reduces DFA polarizabilities and brings them into better agreement with reference values. More recently, SIC polarizabilities were computed to investigate the nature of the bonding in Na(H 2 O) n complexes.…”
Section: Introductionmentioning
confidence: 99%
“…This was shown in terms of several numerical examples in [35,36] where, e.g., the demanding hydrogen chain was found to be reasonably well described within the GS approximation. A key issue for justifying a Slatertype approximation is that the single electron LDA term U LDA [ψ α ] is close enough to the density weighted average (ρ α /ρ) thereof.…”
Section: Comment On the Traditional Sic-slater And Sic-kli Approximationmentioning
confidence: 99%
“…Polarizabilities are a sensitive test case for density functional approaches [36,[59][60][61][62][63][64][65]. We will thus discuss this issue here for three sufficiently different systems.…”
Section: Polarizabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…etc. The problems are particularly dramatic in systems where long-range interactions play a crucial role, i.e., elongated molecules and atomic chains [6][7][8][9][10][11][12][13]. The main origin for these errors is the wrong (exponential) asymptotic behavior and the lack of the derivative discontinuity in the xc potential.…”
Section: Introductionmentioning
confidence: 99%